A Novel Pulmonary Valve Replacement Surgery Strategy Using Contracting Band for Patients With Repaired Tetralogy of Fallot: An MRI-Based Multipatient Modeling Study - Yu, Han; del Nido, Pedro J.; Geva, Tal; Yang, Chun; Wu, Zheyang; Rathod, Rahul H.; Huang, Xueying; Billiar, Kristen L.; Tang, Dalin (Frontiers in Bioengineering and Biotechnology, 2021)
Patients with repaired Tetralogy of Fallot (ToF), a congenital heart defect which includes a ventricular septal defect and severe right ventricular outflow obstruction, account for the majority of cases with late onset right ventricle (RV) failure. Current surgery procedures, including pulmonary valve replacement (PVR) with right ventricle remodeling, yield mixed results. PVR with active band insertion was hypothesized to be of clinical usage on improving RV function measured by ejection fraction (EF). In lieu of risky open-heart surgeries and experiments on animal and human, computational biomechanical models were adapted to study the impact of PVR with five band insertion options. Cardiac magnetic resonance (CMR) images were acquired from 7 TOF patients before PVR surgery for model construction. For each patient, 5 different surgery plans combined with passive and active contraction band with contraction ratio of 20%, 15% and 10% were studied. Those 5 plans include 3 single-band plans with different band locations; 1 plan with 2 bands, and 1 plan with 3 bands. Including the 7 no-band models, 147 computational bi-ventricle models were constructed to simulate RV cardiac functions and identify optimal band plans. Patient variations with different band plans were investigated. Surgery plan with 3 active contraction bands and band active contraction ratio of 20% had the best performance on improving RV function. The Mean±SD RV ejection fraction value from the 7 patients was 42.90%±5.68%, presenting a 4.19% absolute improvement or a 10.82% relative improvement, when compared to the baseline models (38.71%±5.73%, p=0.016). The EF improvements from the 7 patients varied from 2.87% to 6.01%. Surgical procedures using active contraction bands have great potential to improve RV function measured by ejection fraction for patients with repaired ToF. It is possible to have higher right ventricle ejection fraction improvement with more bands and higher band active contraction ratio. Our findings with computational models need to be further validated by animal experiments before clinical trial could become possible.